Harnessing polyphenol power by targeting eNOS for vascular diseases. Issue 14 (30th May 2023) - Das, Mamali; Devi, Kasi Pandima; Belwal, Tarun; Devkota, Hari Prasad; Tewari, Devesh; Sahebnasagh, Adeleh; Nabavi, Seyed Fazel; Khayat Kashani, Hamid Reza; Rasekhian, Mahsa; Xu, Suowen; Amirizadeh, Mehran; Amini, Kiumarth; et al.
Abstract: Vascular diseases arise due to vascular endothelium dysfunction in response to several pro-inflammatory stimuli and invading pathogens. Thickening of the vessel wall, formation of atherosclerotic plaques consisting of proliferating smooth muscle cells, macrophages and lymphocytes are the major consequences of impaired endothelium resulting in atherosclerosis, hypercholesterolemia, hypertension, type 2 diabetes mellitus, chronic renal failure and many others. Decreased nitric oxide (NO) bioavailability was found to be associated with anomalous endothelial function because of either its reduced production level by endothelial NO synthase (eNOS) which synthesize this potent endogenous vasodilator from L-arginine or its enhanced breakdown due to severe oxidative stress and eNOS uncoupling. Polyphenols are a group of bioactive compounds having more than 7000 chemical entities present in different cereals, fruits and vegetables. These natural compounds possess many OH groups which are largely responsible for their strong antioxidative, anti-inflammatory antithrombotic and anti-hypersensitive properties. Several flavonoid-derived polyphenols like flavones, isoflavones, flavanones, flavonols and anthocyanidins and non-flavonoid polyphenols like tannins, curcumins and resveratrol have attracted scientific interest for their beneficial effects in preventing endothelial dysfunction. This article will focus on in vitro as well as in vivo and clinical studies evidences of the polyphenols with eNOS modulating activity against vascular disease condition while their molecular mechanism will also be discussed.